Younger Dryas and Holocene environmental change at the Atlantic fringe of Europe derived from lake‐sediment stable‐isotope records from western Ireland. (26th December 2019) - Holmes, Jonathan A.; Leuenberger, Markus; Molloy, Karen; O'Connell, Michael
Abstract : Western Ireland lies at the Atlantic fringe of Europe and is thus well positioned to record changes in climate linked to North Atlantic circulation. Lake‐sediment oxygen and carbon isotopes are sensitive to changes in the atmosphere, the lake catchment and the lake itself, and thus are valuable proxies for long‐term environmental change. Here we present Younger Dryas and Holocene stable‐isotope records from endogenic and biogenic carbonates from An Loch Mór, a karstic lake on Inis Oírr, Aran Islands, western Ireland. The bulk carbonate and ostracod‐derived stable‐isotope records are a complex response to regional climatic and local factors. Low oxygen‐isotope and high carbon‐isotope values in the Younger Dryas most likely reflect low air temperatures and dominance of bedrock‐derived carbon from the poorly vegetated catchment, but input of detrital carbonate cannot be ruled out. Holocene variations in oxygen‐isotope values are likely a response mainly to changes in the isotopic composition of rainfall, evaporative enrichment of lake water and, during the past millennium, incursion of seawater as a result of regional sea‐level rise. A reduction in carbon‐isotope values at the Younger Dryas/Early Holocene transition reflects increased input of soil‐derived carbon to the lake, modified by changes in aquatic productivity. During the past millennium a shift to less negative values is attributed mainly to increasing saline influence. Broad similarities with stable‐isotope records from other sites in western Ireland suggest regional climatic controls dominated by North Atlantic atmospheric circulation patterns, although abrupt events, that were possibly unique to An Loch Mór, point to local factors also being important.